Glioblastoma Multiforme Stem Cells - Irena Dimov; Deasanka Tasic-Dimov; Irena Conic; Vladisav Stefanovic (The Scientific World Journal)
Glioblastoma multiforme (GBM) is an aggressive, malignant, and lethal brain tumor, resistant to all current forms of treatment. The rapidly emerging focus on cancer stem cells embodies a paradigm shift in our understanding of tumor pathogenesis, while the development of powerful genome-wide screening techniques has provided cause for optimism related to the development of more reliable therapies primarily targeting GBM stem cells (GBMSCs). There are promising mounting data on providing new molecular targets and predictive markers of response, leading to more effective therapies of GBM, guided by patient-specific genetic and epigenetic profiling. However, the achievement of efficient GBMSC targeting also requires an adequate understanding of the unique microenvironment, and the relationship with the immune system in the central nervous system (CNS) and CNS tumors. The endogenous immune regulation is likely to limit or abrogate the efficacy of the host's immune response, as well as the developed immunotherapeutic strategies at present. Therefore, a comprehensive understanding of the mechanisms underlying the GBM-induced immunosuppression is indispensable. This review presents a summary of the present knowledge both on GBMSCs and the GBM, and/or GBMSC-related mechanisms of developing both local and systemic immunosuppression, of which an understanding may lead to the development of the novel and effective therapeutic strategies.